An analysis of the high tropospheric wind circulation Over India in winter - Koteswaram, P. (MAUSAM, 1953)
The distribution of winds and temperature at various heights along roughly longitude 80°E has been discussed for two days of approximately westerly flow in winter, The existence of "jet streams" over Northern India in the high troposphere is observed and the thermal and wind structures associated with the streams are discussed. It is observed that on 30 January 1951, the jet stream occurred in association with a break in the, tropopause as m middle latitudes while on 2 February 1951,lt was found entirely in the tropical troposphere, The former is classified as the polar front type and the latter as the sub-tropical type as postulated by Palmen.